2012
DOI: 10.5668/jehs.2012.38.6.520
|View full text |Cite
|
Sign up to set email alerts
|

Research on Bacterial Distribution of Public Lavatory

Abstract: Objective: This study was performed to assess bacterial distribution concerned in sanitation management of public lavatory in Seoul. Methods: In this research, bacteriological investigation on public lavatory was accomplished for bidet water, bidet nozzle, washbowl and lavatory stool in the 50 public facilities such as public institutions, subway stations, cinema, department stores, large-scale buildings and hospitals amount to 374 specimens. Results: The geometric mean of colony forming unit(CFU) in total aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…What's more, the distribution of the bioaerosols by airflow and traffic of occupants throughout the same home may have also contributed to the similarity among the different rooms in the same home, 22,38,70 with the exception of bathroom and kitchen in which more moisture and microbial sources were present, such as toilets, showering, and faucet 4,5,39 . We have found that the bathroom and kitchen typically harbor higher bioaerosols than other rooms, which agrees well with previous studies 15,74,75 . On the one hand, the use of toilets, showering, and faucet in the bathroom and kitchen could generate a great number of bioaerosol particles.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…What's more, the distribution of the bioaerosols by airflow and traffic of occupants throughout the same home may have also contributed to the similarity among the different rooms in the same home, 22,38,70 with the exception of bathroom and kitchen in which more moisture and microbial sources were present, such as toilets, showering, and faucet 4,5,39 . We have found that the bathroom and kitchen typically harbor higher bioaerosols than other rooms, which agrees well with previous studies 15,74,75 . On the one hand, the use of toilets, showering, and faucet in the bathroom and kitchen could generate a great number of bioaerosol particles.…”
Section: Discussionsupporting
confidence: 89%
“…4,5,39 We have found that the bathroom and kitchen typically harbor higher bioaerosols than other rooms, which agrees well with previous studies. 15,74,75 On the one hand, the use of toilets, showering, and faucet in the bathroom and kitchen could generate a great number of bioaerosol particles. It was reported that up to 145,000 bioaerosols particles were produced from toilets after each flushing 4,64 and millions of bioaerosols particles were produced during showering and faucet.…”
Section: Discussionmentioning
confidence: 99%